Solar power and energy storage systems - Kim, Hee-Je (Singapore, Pan Stanford Publishing, 2019)
Extensive study of solar energy is increasing as fast as the threat of global warming is getting serious. Solar energy is considered the best source of renewable energy because it is clean and unlimited. Solar radiation can be harnessed and converted into different forms of energy that does not pollute the environment. In order to transform solar radiation, we need collectors of sunlight, such as solar cells. The main challenges are energy security, the increasing prices of carbon-based energy sources, and global warming. We cannot use sunlight during the night, so an energy storage system (ESS) is necessary. The best ESS is one with high power and high energy density. This book introduces the basic concepts of an ESS. Written by Prof. Hee-Je Kim, who leads an interdisciplinary team at the Pusan National University, this book compiles and details the cutting-edge research that is revolutionizing solar energy by improving its efficiency and storage techniques through the development of engineered sunlight. It discusses the fabrication and commercialization of next-generation solar cells such as dye-synthesized, quantum-dot, and perovskite solar cells, besides describing the high-energy and power-density-flexible supercapacitor for a hybrid ESS, as well as the dual active bridge (DAB), DC/DC converter, MPPT, PV inverter, and remote control by a smartphone with a novel algorithm for a power-conditioning system.
4.5.2 Conergy NPC Inverter4.6 NPC-Derived Inverter Topologies: An Overview; 4.7 Typical PV Inverter Structures; 4.8 Generic Control Structure for a Single-Phase Grid-Connected System; 5: Facile One-Step Synthesis of a Composite CuO/Co3O4 Electrode Material on Ni Foam for Flexible Supercapacitor Applications; 5.1 Overall Survey; 5.2 Materials and Methods; 5.3 Experiments; 5.3.1 Materials Preparation of Co3O4 and CuO/Co3O4; 5.3.2 Characterization; 5.3.3 Electrochemical Measurements; 5.4 Conclusions; 6: Hybrid Reduced-Graphene Oxide/MnSe2 Cubes: A New Electrode Material for Supercapacitors
OCLC-licensed vendor bibliographic record.
Keywords: Solar energy; Energy storage; Energy storage -- Equipment and supplies; Energy conversion; TECHNOLOGY & ENGINEERING / Mechanical; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Physics